PENGARUH BERMAIN FINGER PAINTING TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI RA. AL MUHAJIRIN BEKASI - Yuli Pujianti; Sumaryati Sumaryati; Purwani Kusumawati Wijaya Kusumawati Wijaya (STIT Al-Marhalah Al-Ulya Bekasi, 2023)
ABSTRACTThe fine motor skills of children aged 5-6 years at RA Al Muhajirin Bekasi have not developed properly, so there needs to be an effort to develop these fine motor skills. This study aims to obtain empirical data regarding the significant effect of playing finger painting on the fine motor skills of children aged 5-6 years at RA Al Muhajirin Bekasi.The research method used in this thesis is a quantitative research method of experimental type. The experimental method is a research method to find the effect of certain treatments on others under controlled conditions. The research design used a true experimental design with a posttest-only control design technique. Posttest-only control design is an experimental research design in which two groups are selected randomly, the first group is given treatment and the other group is not given treatment. The data collection method used an observation sheet in the form of a checklist that measures the fine motor skills of children aged 5-6 years.The results of the post-test data analysis showed that the level of fine motor development of children treated with finger painting was higher (42.75) than the group of children who were not treated with finger painting (35.08). The results of hypothesis testing using the t-test which compares the average post-test scores obtained tcount = 5.110 and Sig. (2-tailed) = 0.000, with ttable = 2.22. Because the value of tcount is greater than ttable and the value of Sig. (2-tailed) is less than 0.05, then